β-Catenin Is Required for Prostate Development and Cooperates with Pten Loss to Drive Invasive Carcinoma - Francis, Jeffrey C. (Public Library of Science, 2013)
Prostate cancer is a major cause of male death in the Western world, but few frequent genetic alterations that drive prostate cancer initiation and progression have been identified. β-Catenin is essential for many developmental processes and has been implicated in tumorigenesis in many tissues, including prostate cancer. However, expression studies on human prostate cancer samples are unclear on the role this protein plays in this disease. We have used in vivo genetic studies in the embryo and adult to extend our understanding of the role of β-Catenin in the normal and neoplastic prostate. Our gene deletion analysis revealed that prostate epithelial β-Catenin is required for embryonic prostate growth and branching but is dispensable in the normal adult organ. During development, β-Catenin controls the number of progenitors in the epithelial buds and regulates a discrete network of genes, including c-Myc and Nkx3.1. Deletion of β-Catenin in a Pten deleted model of castration-resistant prostate cancer demonstrated it is dispensable for disease progression in this setting. Complementary overexpression experiments, through in vivo protein stabilization, showed that β-Catenin promotes the formation of squamous epithelia during prostate development, even in the absence of androgens. β-Catenin overexpression in combination with Pten loss was able to drive progression to invasive carcinoma together with squamous metaplasia. These studies demonstrate that β-Catenin is essential for prostate development and that an inherent property of high levels of this protein in prostate epithelia is to drive squamous fate differentiation. In addition, they show that β-Catenin overexpression can promote invasive prostate cancer in a clinically relevant model of this disease. These data provide novel information on cancer progression pathways that give rise to lethal prostate disease in humans.